Pulsed electrochemical and electroless techniques for efficient removal of Sb and Pb from water. Issue 12 (9th November 2018) - Mosivand, Saba; Monzon, Lorena M. A.; Kazeminezhad, Iraj; Kumar, Anup; Coey, J. Michael D.
Abstract : Two innovative electrochemical approaches for removing both antimony and lead from water using sacrificial iron sheets are reported; a pulsed method for fast coagulation and a slower electroless method with high efficiency, low cost and no requirement for electrical energy. The study covers laboratory samples and mine wastewater. Abstract : Pulsed electrochemical and electroless techniques for removing antimony and lead from water using sacrificial iron sheets are analyzed in terms of number of pulses and electrolysis time (up to 20 minutes), or pH and exposure time (up to 12 days) respectively. The amount of Sb or Pb in a test aqueous solution containing 10 ppm could be reduced to <0.02 ppm by either method. The electroless method was particularly effective for antimony removal at low pH. These protocols were also successful for removing antimony from mine wastewater containing 0.16 ppm Sb. The pulsed method leads to magnetite-rich antimony-containing sludge that can be removed magnetically, and the electrogenerated sludge was characterized both structurally and magnetically using X-ray diffraction, magnetometry and Mössbauer spectroscopy. Lead is preferably removed from mixed-aqueous solutions containing 5 ppm each of Sb and Pb. The findings were in agreement with either Langmuir or Freundlich adsorption isotherms. Results are compared with those of other methods for antimony or lead removal from wastewater.